Associations between media use and health information-seeking behavior on vaccinations in South Korea - Jiyeon Kim; Minsoo Jung (BMC, 2017)
Abstract Background Although vaccinations are critical for preventing emerging infectious diseases, scant research has been conducted on risk communication. With socio-economic characteristics, health behavior, and underlying diseases under control, we investigated associations between media use, health information-seeking behavior, health information type, and vaccination in the population. Methods This study relied on a national survey of Korean adults (n = 1367). Participants were adult males and females age 20 and older. Web and face-to-face surveys were conducted throughout July 2014. The main outcome was vaccination (categorized as yes or no). Independent variables were time spent on media, frequency of health information-seeking behavior, and types of health information sought. Results Controlling for co-variates, logistic regression analysis was conducted to identify factors that influence Korean adults being vaccinated. Results revealed that accessible information about emerging infectious diseases, listening to the radio, and reading the newspaper were associated with increased odds of being vaccinated. Active seeking health information as well as being female and of higher socio-economic status were positively correlated with Korean adults being vaccinated. Conclusion It is critical to promote health information-seeking behavior and use diverse media channels to increase acceptance and awareness of emerging infectious diseases and vaccinations. Because there are differences in vaccination awareness depending on social class, it is critical to reduce communication inequality, strengthen accessibility to vaccinations, and devise appropriate risk communication strategies that ensure Korean adults receive vaccinations.